1993
DOI: 10.1002/stem.5530110625
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of survival and proliferation by interleukin 3, fcil‐ligand and erythropoietin on early and late appearing spleen colony forming units in culture

Abstract: Abstract. We examined the effects of interleukin 3 (IL-3), kit-ligand and erythropoietin (EPO) on the survival and growth of early appearing spleen colony forming units (CFU-Ss) and late appearing CFU-S (CFU-SI2) in short-term liquid culture (SLC). In the control cultures, without any additive, CFU-S8 and CFU-SI2 declined; nearly 10% of the initial number of CFU-S still survived by the second day of culture. The addition of IL-3 or kit-ligand increased the survival both of CFU-S8 and CFU-S12, with an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The present findings on CD34 / CD38 0 BM progenitor and suppress apoptosis of primitive murine hematopoietic cells were in agreement with those previously made on canprogenitor cells, 4,6-14,37,49,50 less is known about the ability of didate murine stem cell populations, [8][9][10][11][12][13][14] in that IL-3, KL, and cytokines to promote viability of populations of candidate FL can directly promote viability of primitive progenitor human stem cells.…”
Section: Distinction Between the Ability Of Tpo And Epo To Promotesupporting
confidence: 91%
See 3 more Smart Citations
“…The present findings on CD34 / CD38 0 BM progenitor and suppress apoptosis of primitive murine hematopoietic cells were in agreement with those previously made on canprogenitor cells, 4,6-14,37,49,50 less is known about the ability of didate murine stem cell populations, [8][9][10][11][12][13][14] in that IL-3, KL, and cytokines to promote viability of populations of candidate FL can directly promote viability of primitive progenitor human stem cells.…”
Section: Distinction Between the Ability Of Tpo And Epo To Promotesupporting
confidence: 91%
“…Address reprint requests to Ole J. Borge, MSc, Stem Cell Laborareconstituting stem cells, and that it can maintain the majority of such progenitor cells viable after prolonged culture. [11][12][13] Sweden. In contrast, studies of human CD34 / DR 0 BM progenitor The publication costs of this article were defrayed in part by page cells as well as CD34 / CD38 0 fetal liver cells have reported charge payment.…”
Section: Tive Murine Progenitor Cells Including Pluripotent Long-termmentioning
confidence: 99%
See 2 more Smart Citations
“…The viability and proliferation of haematopoietic cells are strictly dependent on haematopoietic cytokines (Williams et al 1990), and haematopoietic cells die by apoptosis in the absence of cytokines, whereas malignant cells release cytokines in an autocrine manner (Kinoshita et al 1995;Lotem and Sachs 1999). Several studies have shown that cytokines promote viability and supress apoptosis in haematopoietic progenitor cells (Williams et al 1990;Ikebuchi et al 1988; Williams and Broxmeyer 1988;Bodine et al 1991;Itoh et al 1992;Katayama et al 1993;Sasaki et al 1993;Li and Johnson 1994;Jacobsen et al 1995;Keller et al 1995;Rasko et al 1995;Lotem and Sachs 1995;Metcalf 2008;Bordoni et al 2018). Cytokines can also protect cells from apoptotic death caused by chemotherapeutic agents and can decrease their toxic effects on haematopoietic cells (Griffin and Löwenberg 1986;Lotem and Sachs 1999;Zeuner et al 2003).…”
Section: Introductionmentioning
confidence: 99%